Design of the Feeding Frog Cognitive Game for Early Childhood using the Mechanics, Dynamics, and Aesthetics (MDA) Framework and Greenfoot - Hayat, Cynthia (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
This study aims to design a cognitive game that stimulates early childhood motor development while introducing knowledge about animals and their types of food. The development of the game utilizes the Mechanics, Dynamics, and Aesthetics (MDA) framework along with the Greenfoot software. The mechanics component includes genre, objectives, platform, rating, levels, and artistic concept. The dynamics component covers storyline, gameplay controls, challenges, and game rules, while the aesthetics component emphasizes sensation, narrative, engagement, and fantasy. Players interact with the game by feeding animals based on their appropriate diets. The storyline centers on various animal habitats, where each level represents an environment with increasing difficulty—basic, intermediate, and advanced—while also providing motor stimulation. Participatory observation was conducted in several playgroups in West Jakarta to gain insights into the game's impact and identify the key elements that capture players’ interest. Evaluation of user responses showed that out of seven assessed statements, five received a